(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Urban kampongs, which are essential components of urban structures, undergo continuous changes alongside city growth and development. However, these areas often experience significant social issues in developing countries, including Indonesia. The Jakarta Provincial Government has recently undertaken efforts to improve the quality of urban kampongs in Jakarta, one of which is the revitalization of Akuarium Kampong. This once-dilapidated kampong has been transformed into a vertical kampong block with modern and improved building standards through a challenging process. Given the relatively representative physical condition of the buildings, a key question arises: How satisfied are the residents with these changes? Therefore, this study aimed to explore the relationship between the improvement in the physical quality of urban kampongs, specifically Akuarium Vertical Kampong, and the satisfaction level of its residents within the context of global sustainable development goals. A mixed-method approach was employed to achieve a comprehensive understanding, which combined quantitative and qualitative analysis. The results showed that the improved quality of Akuarium Kampong led to a reasonably high level of satisfaction among its residents, particularly regarding the physical and social environmental aspects. However, the economic aspect remained a challenge, as it does not yet meet satisfactory levels. Several factors contributed to this problem, with a significant issue being the absence of new income sources for most residents.